2015
DOI: 10.2337/dc15-0730
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Self-management Education and Support in Type 2 Diabetes: A Joint Position Statement of the American Diabetes Association, the American Association of Diabetes Educators, and the Academy of Nutrition and Dietetics

Abstract: Diabetes is a chronic disease that requires a person with diabetes to make a multitude of daily self-management decisions and to perform complex care activities. Diabetes self-management education and support (DSME/S) provides the foundation to help people with diabetes to navigate these decisions and activities and has been shown to improve health outcomes (1-7). Diabetes self-management education (DSME) is the process of facilitating the knowledge, skill, and ability necessary for diabetes self-care. Diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
555
0
40

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 618 publications
(616 citation statements)
references
References 73 publications
5
555
0
40
Order By: Relevance
“…Diabetes self-management education has been used to encourage lifestyle changes and improve medication compliance 4 . The efficacy of diabetes mellitus education has been widely accepted, and the certificated diabetes educator (CDE) is considered an important member of the multidisciplinary team responsible for patient care 5,6 . However, the efficacy of education in terms of HbA1c reduction has not been consistently demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes self-management education has been used to encourage lifestyle changes and improve medication compliance 4 . The efficacy of diabetes mellitus education has been widely accepted, and the certificated diabetes educator (CDE) is considered an important member of the multidisciplinary team responsible for patient care 5,6 . However, the efficacy of education in terms of HbA1c reduction has not been consistently demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Regarding DSME, studies have shown improved outcomes such as decreasing Hb A1c level, receiving care within recommended guidelines, and adhering to prescription regimens leading to lower utilization trends. [16,18,28,29] Still, only 56.7% of Missouri diabetics have ever attended a DSME class, which is below the Healthy People 2020 goal of 62.5%. [1] Our results also suggest that those who visit with a nutritionist or diabetes educator have more knowledge to manage their diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[17] The seven key areas that self-care focus on include healthy eating, being active, monitoring blood sugars, medication adherence, problem solving for diabetes control, healthy coping, and reducing risks of complications. [18] While healthy eating incorporates many aspects, CC is one of the tools that may be needed, depending on an individual's goals. [9] The approach used in diabetes education is not only education of the patient but also the integration of techniques that promote effective self-management, such as goal setting and follow up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing prevalence of T2DM will put pressure on health systems to appropriately manage these patients to avoid diabetic complications. Optimizing self-management of glycemic control and other risk factors in conjunction with pharmacologic therapy may be an efficient way to improve patient outcomes [2][3][4][5]. While selfmanagement has been traditionally in person educational programs that are resource intensive, advances in mobile technology now provide the opportunity to deliver effective self-management support to patients in a convenient and potentially cost effective manner [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%